Teaching work, fundamental rights and protection of personal data in the technological Society (Research, Society and Development, 2022)
The object of discussion of this article is the analysis of the relationship between teaching work, fundamental rights and protection of personal data in the technological society, in order to reflect on the process of intensifying the use of digital technologies in education, in order to know possible violations to the fundamental rights of subjects. The investigation used the methodology of bibliographical and documental research based on a dialectical materialist approach from the following question: to what extent does the stimulated insertion of digital technologies in education violate the fundamental rights of individuals? Among the results, it can be seen that the intensified use of digital technologies has a negative impact on teaching work relationships, as well as on the subjects' rights to privacy. In conclusion, it is highlighted that, for the work relationships of these professionals not to be negatively impacted by the use of technologies and to overcome the lack of privacy and protect the personal data of individuals in the technological society, we can base ourselves on the Freirean strategy of awareness of teachers and students about the pedagogical work, in addition to the strategy of the paradigm of the City of Feenberg, whose challenge is the use of technologies to be appropriated in a dialogic way.